A cinnamoyl substituted Nile Red-based probe to detect hydrazine. Issue 24 (14th June 2017) - Jiang, Xin-Dong; Guan, Jian; Bian, Hui; Xiao, Yi
Graphical abstract: Nile Red-based probe with a new recognition unit (cinnamoyl) was highly selective and sensitive to N2 H4 . Because the combination of the π-π conjugate system can stabilize the ethylene union, the nucleophilic addition of the thiol group of Cys/Hcy becomes non-effective. Highlights: Nile Red-based probe with a new recognition unit (cinnamoyl) was highly selective and sensitive to N2 H4 . The combination of the π-π conjugate system can stabilize the ethylene union. The nucleophilic addition of the thiol group of Cys/Hcy becomes non-effective. Hydrazinolysis by N2 H4 generated Nile Red derivative was advocated and feasible. Abstract: Herein we discovered that a Nile Red-based probe with a cinnamoyl unit was highly selective and sensitive to N2 H4 . Hydrazinolysis by N2 H4 would release a hydroxyl substituted Nile Red and result in remarkable fluorescence quench. Importantly, Cys/Hcy would not interrupt the N2 H4 recognition. This is because, for this probe, the combination of the π-π conjugate system can stabilize the ethylene union, which results in the nucleophilic addition of the thiol group of Cys/Hcy becomes non-effective.